India’s diplomatic strategy in great power rivalry - Park, Yong Soo (International Journal of Social Sciences Perspectives, 2025)
This study explores the essence and key characteristics of India’s diplomatic strategy amid the competition between the United States and the China-Russia bloc. As the unipolar order dominated by the United States declines, the world has entered an era of multipolar great-power politics, defined by intense security competition between these blocs. In this shifting global landscape, India has anchored its foreign policy in a strategy of hedging. Rather than aligning exclusively with or balancing against any single major power, India has adopted a clear principle of maintaining balanced relationships with all key players. Taking a neutral stance, India has built a complex web of bilateral and multilateral partnerships with all major powers across political, economic, and security domains. Through this carefully crafted hedging strategy, India preserves its strategic autonomy, ensuring the flexibility needed to navigate diverse diplomatic challenges. At the same time, this approach enables India to maximize its national interests amidst global uncertainties while strengthening its position on the world stage.